1998
DOI: 10.1104/pp.117.4.1515
|View full text |Cite
|
Sign up to set email alerts
|

cis -Isomers of Cytokinins Predominate in Chickpea Seeds throughout Their Development1

Abstract: Trans-isomers of cytokinins (CK) are thought to predominate and have greater biological activity than corresponding cis-isomers in higher plants. However, this study demonstrates a system within which the predominant CK are cis-isomers. CK were measured at four developmental stages in developing chickpea (Cicer arietinum L. cultivar Kaniva) seeds by gas chromatography-mass spectrometry. Concentrations were highest at an early endospermic fluid stage and fell considerably when the cotyledons expanded. Seed tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
80
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(92 citation statements)
references
References 33 publications
7
80
0
Order By: Relevance
“…The biosynthetic pathway of cytokinins has not been demonstrated clearly (Moore, 1989;Binns, 1994), and further study is needed to determine if the cytokinins contained in racemes come from the roots or from other parts of the plants, and to learn how the cytokinin forms are altered during the transition. In chickpeas, cis-isomers were found to be predominant in seeds (Emery et al, 1998), while transisomers are the more commonly reported forms in higher plants (McGaw and Burch, 1995 ;Prinsen et al, 1997). A comparison among floral positions of the peak cytokinin amount, which was observed at 10 DAA, revealed that the concentration was the highest at the most proximal positions ( 1 -4) of racemes, followed by the middle positions (moderate concentration) and the distal positions where the concentration was extremely low (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The biosynthetic pathway of cytokinins has not been demonstrated clearly (Moore, 1989;Binns, 1994), and further study is needed to determine if the cytokinins contained in racemes come from the roots or from other parts of the plants, and to learn how the cytokinin forms are altered during the transition. In chickpeas, cis-isomers were found to be predominant in seeds (Emery et al, 1998), while transisomers are the more commonly reported forms in higher plants (McGaw and Burch, 1995 ;Prinsen et al, 1997). A comparison among floral positions of the peak cytokinin amount, which was observed at 10 DAA, revealed that the concentration was the highest at the most proximal positions ( 1 -4) of racemes, followed by the middle positions (moderate concentration) and the distal positions where the concentration was extremely low (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…All samples were evaporated to dryness in a speed vacuum concentrator at 35°C and immediately stored at −20°C. CKNTs were dephosphorylated using 3 units of bacterial alkaline phosphatase in 1 ml 0.1 M ethanolamine-HCl (pH 10.4) for 12 hours at 37°C (Emery et al, 1998). The resulting CKRs were brought to dryness in a speed vacuum concentrator at 35°C.…”
Section: Measurements Of Endogenous Abscisic Acid and Cytokinins Levementioning
confidence: 99%
“…Furthermore, in a bacterial system, the maize cytokinin receptor ZmHK1 responded to cZ and tZ with comparable affinities (Yonekura-Sakakibara et al, 2004;Lomin et al, 2011). cZ and its derivatives are abundant not only in maize but also in other species, including chickpea (Cicer arietinum; Emery et al, 1998) and rice (Oryza sativa; Takagi et al, 1985Takagi et al, , 1989Kojima et al, 2009). In addition, a recent comprehensive screen showed that higher levels of cZ than tZ derivatives can be found in species across the complete evolutionary tree of land plants (Gajdošová et al, 2011).…”
mentioning
confidence: 99%